Developing A Functional Model for Effective Education Based on Adaptive Content, Personalization, Inclusive Interface, And Feedback Mechanisms - Kayumova Nazokat Rashitovna (European International Journal of Pedagogics, 2025)
This article presents the development of a functional model that integrates adaptive content, personalization, inclusive interface, and feedback mechanisms to ensure effective education within the framework of digital pedagogy. The main goal of the study is to create a learner-centered digital learning environment that considers the needs, abilities, and learning conditions of each student. The model is based on the principles of Universal Design for Learning (UDL), Bloom's taxonomy, metacognitive approaches, and the capabilities of artificial intelligence (AI). It integrates modular and differentiated content delivery, AI-driven personalized learning paths, an interface compliant with WCAG 2.1 accessibility standards, and intelligent feedback systems into a unified structure. The proposed functional model is not only scientifically grounded but also technologically viable and ready to be implemented into local educational platforms. It serves as a comprehensive solution for enhancing teaching effectiveness, ensuring inclusivity, and advancing the quality of digital pedagogy.